Hydrophobic membrane development for membrane contactor by electrospinning - Ng, Terence Yam Hui (2015)
Over the years, membrane contactor (MC) is slowly replacing the conventional methods of CO2 separation. Its equipment is less complex, flexible for scaling up or down, and has a lower footprint and chemical usage. The common limitations of MC applications are low gas flux and a gradual process of wetting during long term operations. The possible solutions are to fabricate a newly designed highly porous membrane with high hydrophobicity which can both increase gas flux and reduce membrane wetting. This paper focused on a unique technique called electrospinning to fabricate MC membranes. Two polymers, polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE) are chosen to make the polymer dope solutions to fabricate the MC membranes. A common characteristic between both polymers is that they contain carbon-fluorine (CF) bonds. After electrospinning the dope solution, PTFE nanoparticles were incorporated in the PVDF nanofibers to enhance membrane hydrophobicity. These in-house nanofiber membranes have been characterised and tested against the commercial PVDF membrane in the MC performance test. Characterisation test results showed that the electrospinning produced a membrane composed of nanofibers overlapping each other. This morphology significantly increased the membrane’s porosity which can reduce mass transfer resistance in MC. An optimal quantity of PTFE nanoparticles within the membrane increased membrane porosity and enhanced thermal resistance as a higher temperature was required to degrade the membrane polymers completely. PTFE also increased the membrane surface hydrophobicity as the water contact angle of the membrane has been changed from 131.4o to 136.3o. Additionally, the incorporation of PTFE nanoparticles improved membrane anti-wetting properties as the liquid entry pressure (LEP) of the membrane increased from 1.38 bars to 1.72 bars. These improvements allowed the gas flux to increase from 4.3510-3 mol/m2s to 4.810-3 mol/m2s. Moreover, the MC showed a reasonably stable performance throughout the 31 days long-term operation using a 2 M sodium taurinate aqueous solution as the liquid absorbent and pure CO2 as the feed gas. The chemical compatibility test indicated that after the long-term constant contact with the sodium taurinate, the hydrophobicity of the PVDF/PTFE composite nanofibrious membrane was still maintained.